A method for preparing a molybdenum-sodium alloy target with high coating performance
During the preparation process of molybdenum sodium alloy target, the process of pre-firing of mixed powder medium-frequency furnace, re-crumbing of powder, stirring, mixing and screening of powder, and pressing of oil presses, the problems of Na element segregation and volatility loss are solved, and the density and coating performance of the target material are improved.
Patent Information
- Application Number
- CN202411297361.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Traditional molybdenum sodium alloy targets are prone to segregation and volatility loss of Na elements during the preparation process, resulting in poor coating performance and low photoelectric conversion efficiency of thin films, and slightly low density, which affects performance.
By mixing molybdenum powder and sodium molybdate aqueous solution, drying, grinding and sieving, a uniform mixed powder is formed, and then sintering and grinding is carried out in a medium-frequency furnace. Finally, the target is prepared by a hydraulic press to avoid segregation and volatility of Na elements during high-temperature sintering.
The distribution uniformity of Na elements in alloy targets is improved, the density and coating performance of the targets are improved, and the photoelectric conversion efficiency of the thin film is improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of target material preparation, and in particular relates to a method for preparing a molybdenum-sodium alloy target material with high coating performance. Background Art
[0002] Molybdenum-sodium alloy products are mainly used in solar thin-film cells. Research has found that adding a layer of molybdenum-sodium alloy coating to the bottom plate of thin-film solar cells can greatly improve the photoelectric conversion efficiency of the cells. At present, the solar cell products used in the photovoltaic industry are developing from the first generation of polycrystalline silicon solar cells to the second generation of thin-film solar cells. At the same time, flexible thin-film solar cell technology is also developing rapidly.
[0003] However, the molybdenum-sodium alloy prepared by the traditional process is prone to problems such as poor film-forming performance of the molybdenum-sodium alloy target and poor thin-film photoelectric conversion efficiency due to Na element segregation and volatilization and loss of Na element during high-temperature sintering. In addition, the density of the molybdenum-sodium target manufactured in the prior art is slightly low, which affects its performance. Therefore, how to ensure the uniformity of the distribution of the Na element in the alloy target and how to prevent the volatilization and loss of Na element during the target preparation process, while increasing the density of the molybdenum-sodium target, has become the main means to improve the coating performance of the molybdenum-sodium alloy target and the photoelectric conversion efficiency of the thin film. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a method for preparing a molybdenum-sodium alloy target with high coating performance, which can improve the uniformity of the distribution of the Na element in the alloy target and enhance the density of the molybdenum-sodium target.
[0005] The present invention is achieved through the following technical solutions:
[0006] The present invention provides a method for preparing a molybdenum-sodium alloy target with high coating performance, comprising the following steps:
[0007] Step 1: Select raw materials for preparing molybdenum-sodium alloy, mix them into mixed powder, and set aside;
[0008] Step 2: placing the mixed powder of step 1 in a medium frequency sintering furnace for sintering to obtain Mo-Na alloy sintered powder for standby use;
[0009] Step 3: Grind and sieve the Mo-Na alloy sintered powder obtained by sintering to obtain Mo-Na alloy powder for later use;
[0010] Step 4: Put the Mo-Na alloy powder into a mold and press it to obtain a target blank for later use;
[0011] Step 5: After processing the pressed target blank, a finished Mo-Na alloy target is obtained.
[0012] Furthermore, in step one, molybdenum powder and sodium molybdate powder are selected as raw materials, the sodium molybdate powder is dissolved in water to prepare a sodium molybdate aqueous solution, and then the molybdenum powder and the sodium molybdate aqueous solution are mixed and stirred to obtain a mixture, and the mixture is dried and then ground and sieved to obtain a mixed powder.
[0013] Furthermore, the average particle size of the selected molybdenum powder is 2.2-4.2 μm, the purity of the molybdenum powder is 99.95%, and the purity of the sodium molybdate is 99%.
[0014] Furthermore, among the selected raw materials, based on mass percentage, the sodium molybdate content is 3.1%-31.3%, and the molybdenum powder content is 68.7%-96.9%.
[0015] Furthermore, a solid-liquid mixer is used to mix the molybdenum powder and the sodium molybdate aqueous solution, and the mixing time is 12-24 hours.
[0016] Further, the mixture is placed in a vacuum furnace for drying, and the drying conditions are: temperature 200±20°C, drying time 4-10 h; and a 200-mesh screen is used for screening.
[0017] Furthermore, in step 2, a medium frequency sintering furnace in a hydrogen atmosphere is selected, the sintering temperature is 900-1300° C., and the temperature is kept for 1-2 h.
[0018] Furthermore, a 160-mesh sieve is used for screening in step three.
[0019] Furthermore, in step four, the mold is pressed by a hydraulic press, and the inner surface of the mold is covered with a MoS2 coating with a coating thickness of 0.2-0.4 mm.
[0020] Furthermore, in step 4, the pressing temperature is 550°C-650°C, the pressing pressure is 50Mpa-130Mpa, and the holding time is 10-30min.
[0021] The beneficial effects of the present invention are:
[0022] The present invention first sintered the raw material mixed powder into Mo-Na alloy powder through medium and high temperature, and then ground and crushed it and pressed it into a target material blank. Since Na2MoO4 has a low melting point (Na2MoO4 melting point is 687°C), it tends to melt first during sintering, and the melted Na2MoO4 flows to the downstream side of the spatial position of the alloy structure due to its own gravity and other factors, and causes the segregation of the Na element. In the present invention, the segregation phenomenon occurs during the powder sintering process, and then it is ground and mixed again to make the Mo and Na elements evenly distributed again. No high-temperature sintering is performed subsequently, which avoids the problems of poor coating performance of Mo-Na target material caused by segregation and unevenness of Na element in the traditional pressing and sintering process; and by grinding, mixing and then pressing, the pores generated by the volatilization of Na element during the sintering process are eliminated, the density of the target material is improved, and the high-temperature sintering in the early stage can realize the alloying treatment of molybdenum powder, improve the strength of molybdenum powder, and make it have certain metal properties.
[0023] On the basis of solving the above technical problems, the present invention achieves better technical effects through further technical improvements:
[0024] (1) In the present invention, the solid molybdenum powder and the liquid sodium molybdate aqueous solution are mixed in proportion, and the Na element is introduced through the Na2MoO4 aqueous solution, so that the Na element is evenly coated on the surface of the molybdenum powder particles, thereby improving the uniformity of the Na element distribution in the Mo-Na alloy target.
[0025] (2) Through the cooperation of the rigid mold and the hydraulic press, a Mo-Na tube target with a certain rigidity can be obtained. The pressing temperature in the process is 550℃-650℃, which improves the compression ratio of the tube target, reduces the pores in the tube target, and increases the density of the Mo-Na tube target. While controlling the softening compression ratio of the tube target, it avoids the volatilization of the Na element or secondary segregation due to excessively high temperature.
[0026] (3) By controlling the ratio of Na2MoO4 and molybdenum powder, the reduction in the ratio caused by the volatilization of the Na element during the high-temperature sintering process is compensated. At the same time, the temperature of the high-pressure pressing process is controlled to avoid the volatilization and loss of the Na element, thereby achieving the purpose of controlling the proportion of the Na element.
[0027] (4) Since the Mo-Na alloy billet has a certain degree of adhesion to the mold when it is just prepared, but the Mo-Na alloy billet itself has the characteristics of hardness and brittleness, it cannot be demolded by tapping with a wooden hammer or a rubber hammer like a general metal billet or alloy billet. Therefore, the present invention covers the inner surface of the pressing mold with a MoS2 coating to facilitate the separation of the target material and the mold after the Mo-Na alloy is pressed.
[0028] In summary, the present invention obtains Mo-Na alloy by pre-sintering the mixed powder in a medium frequency furnace, crushing the powder again, stirring, mixing and screening, and pressing with a hydraulic press. The Mo and Na elements in the target are evenly distributed, the O content is ≤5%, and the density is ≥90% of the theoretical density. Its performance is better than that of Mo-Na alloy target products with the same specifications, laying a theoretical and practical foundation for the preparation of high-performance Mo-Na alloy target products for CIGS. DETAILED DESCRIPTION
[0029] A method for preparing a molybdenum-sodium alloy target with high coating performance comprises the following steps:
[0030] Step 1: Select powder
[0031] Molybdenum powder and sodium molybdate powder are selected as powder raw materials for preparing Mo-Na alloy and set aside; the average particle size of the molybdenum powder is 2.2-4.2 μm, the purity of the molybdenum powder is 99.95%, and the purity of the sodium molybdate is 99%;
[0032] Step 2: Mix the powder
[0033] Sodium molybdate is prepared into an aqueous solution, and molybdenum powder and the sodium molybdate aqueous solution are mixed by a PDH-CT solid-liquid mixer for 12 hours to 24 hours to obtain a mixture for standby use; and among the selected raw materials, the sodium molybdate content is 3.1% to 31.3%, and the molybdenum powder content is 68.7% to 96.9% by mass.
[0034] Step 3: Drying, grinding and sieving
[0035] The mixture is placed in a vacuum furnace for drying, then ground and sieved to obtain a mixed powder with uniform particle size for use; the drying conditions are: temperature 200±20℃, drying time 4-10h; a 200-mesh screen is used for sieving.
[0036] Step 4: Sintering in medium frequency furnace
[0037] The mixed powder obtained in step 3 is sintered in a medium frequency sintering furnace in a hydrogen atmosphere at a sintering temperature of 900-1300°C for 1-2 hours to obtain Mo-Na alloy sintered powder. During the sintering process, the powder is freely stacked in the container;
[0038] Step 5: Grinding and sieving
[0039] Grinding and sieving the Mo-Na alloy sintered powder obtained by sintering, using a 160-mesh screen to obtain Mo-Na alloy powder for later use;
[0040] Step 6: Suppression
[0041] The Mo-Na alloy powder is loaded into the mold, and the Mo-Na alloy powder in the mold is pressed by a hydraulic press to obtain a target blank for standby use; and the inner surface of the mold is covered with a MoS2 coating with a coating thickness of 0.2-0.4mm. The pressing temperature is 550℃-650℃, the pressing pressure is 50Mpa-130Mpa, and the holding time is 10-30min.
[0042] Step 7: Turning
[0043] After processing the pressed target material blank, a finished Mo-Na alloy tube target is obtained.
[0044] Step 8: Post-processing
[0045] The products after turning processing are cleaned, inspected and packaged to obtain Mo-Na tube targets with high coating performance.
[0046] Embodiment 1:
[0047] A method for preparing a molybdenum-sodium alloy target with high coating performance comprises the following preparation steps:
[0048] Step 1: Select powder
[0049] The average particle size of molybdenum powder is 2.2μm, the purity of molybdenum powder is: 99.95%, and the purity of sodium molybdate is: 99%;
[0050] Step 2: Mix the powder
[0051] Sodium molybdate is prepared into an aqueous solution, and solid molybdenum powder and liquid sodium molybdate aqueous solution are mixed in proportion using a PDH-CT solid-liquid mixer, wherein, by weight, the sodium molybdate content is 3.1%, and the molybdenum powder content is 96.9%, and the mixing time is 12 hours to obtain a mixture;
[0052] Step 3: Drying, grinding and sieving
[0053] The mixture was placed in a vacuum furnace and dried at 220°C for 4 hours; the dried powder was ground and sieved, and after sieving through a 200-mesh sieve, a Mo-Na alloy powder with uniform particle size was obtained;
[0054] Step 4: Sintering in medium frequency furnace
[0055] The Mo-Na alloy powder obtained in step 3 is sintered at 900° C. in a hydrogen medium frequency sintering furnace and kept warm for 1 hour to obtain a sintered powder, which is freely stacked in a container;
[0056] Step 5: Grinding, mixing and sieving
[0057] The sintered powder is ground, stirred and sieved to obtain a mixed powder with a certain metal strength and uniform particle size. The sieve is a 160-mesh sieve, and the sieve is taken for the next step;
[0058] Step 6: Suppression
[0059] The mixed powder is pressed to obtain a pressed tube blank, the inside of the pressing mold has a coating of MoS2, the coating thickness is 0.2mm; the pressing temperature is 550°C, the pressing pressure is 50Mpa, and the holding time is 30min;
[0060] Step 7: Turning
[0061] The Mo-Na tube target after pressing is turned to obtain a finished Mo-Na alloy tube target;
[0062] Step 8: Post-processing
[0063] The product after the turning process in the previous step is cleaned, inspected and packaged to obtain a Mo-Na tube target with high coating performance.
[0064] After inspection and testing, the molybdenum sodium tube target has a dense structure and good coating performance. The sintering density of the molybdenum sodium tube target is 8.74g / cm 3 (The theoretical density of Mo-Na tube target is 9.57g / cm 3 , that is, the density of the molybdenum-sodium tube target is greater than 90% of the theoretical density), and the powders from the upper, middle and lower areas of the Mo-Na tube target are marked as a, b and c, and the Na content is tested respectively. The test results are: a: 0.95%, b: 0.96%, c: 0.96%.
[0065] It is shown that the density of the Mo-Na alloy can be effectively improved by preparing the Mo-Na alloy by the method of the present invention, and the contents of the Na element at a, b and c are basically the same. It is also shown that the present invention improves the uniformity of the distribution of the Na element in the Mo-Na alloy tube target. At the same time, the high temperature treatment process of the powder is combined with the medium temperature pressing process, so that the Mo-Na alloy has considerable alloying properties and strength, and the coating performance of the Mo-Na alloy tube target is improved in many aspects.
[0066] Embodiment 2:
[0067] A method for preparing a molybdenum-sodium alloy target with high coating performance comprises the following preparation steps:
[0068] Step 1: Select powder
[0069] The average particle size of molybdenum powder is 4.2μm, the purity of molybdenum powder is: 99.95%, and the purity of sodium molybdate is: 99%;
[0070] Step 2: Mix the powder
[0071] Sodium molybdate is prepared into an aqueous solution, and solid molybdenum powder and liquid sodium molybdate aqueous solution are mixed in proportion using a PDH-CT solid-liquid mixer, wherein, by mass percent, the sodium molybdate content is 31.3%, and the molybdenum powder content is 68.7%, and the mixing time is 12 hours to obtain a mixture;
[0072] Step 3: Drying, grinding and sieving
[0073] The mixture was placed in a vacuum furnace and dried at 220°C for 4 hours; the dried powder was ground and sieved, and after sieving through a 200-mesh sieve, a Mo-Na alloy powder with uniform particle size was obtained;
[0074] Step 4: Sintering in medium frequency furnace
[0075] The Mo-Na alloy powder obtained in step 3 is sintered at 1300° C. in a hydrogen medium frequency sintering furnace and kept warm for 1 hour to obtain a sintered powder, which is freely stacked in a container;
[0076] Step 5: Grinding, mixing and sieving
[0077] The sintered powder is ground, stirred and sieved to obtain a mixed powder with a certain metal strength and uniform particle size. The sieve is a 160-mesh sieve, and the sieve is taken for the next step;
[0078] Step 6: Suppression
[0079] The mixed powder is pressed to obtain a pressed tube blank, the inner coating of the pressing mold is MoS2, the coating thickness is 0.4 mm; the pressing temperature is 650°C, the pressing pressure is 130 MPa, and the holding time is 10 min;
[0080] Step 7: Turning
[0081] The Mo-Na tube target after pressing is turned to obtain a finished Mo-Na alloy tube target;
[0082] Step 8: Post-processing
[0083] The product after the turning process in the previous step is cleaned, inspected and packaged to obtain a Mo-Na tube target with high coating performance.
[0084] After inspection and testing, the molybdenum sodium tube target has a dense structure and good coating performance. The sintering density of the molybdenum sodium tube target is 5.84g / cm 3 (The theoretical density of Mo-Na tube target is 6.14g / cm 3, that is, the density of the molybdenum-sodium tube target is greater than 90% of the theoretical density), and the powders from the upper, middle and lower areas of the Mo-Na tube target are marked as a, b and c, and the Na content is tested respectively. The test results are: a: 9.6%, b: 9.6%, c: 9.7%.
[0085] It is shown that the density of the Mo-Na alloy can be effectively improved by preparing the Mo-Na alloy by the method of the present invention, and the contents of the Na element at a, b and c are basically the same. It is also shown that the present invention improves the uniformity of the distribution of the Na element in the Mo-Na alloy tube target. At the same time, the high temperature treatment process of the powder is combined with the medium temperature pressing process, so that the Mo-Na alloy has considerable alloying properties and strength, and the coating performance of the Mo-Na alloy tube target is improved in many aspects.
[0086] Comparative Example 1:
[0087] The only difference between Comparative Example 1 and Example 2 is that in step 4, the Mo-Na alloy powder is first cold isostatically pressed using a flexible mold, and then placed in a medium frequency furnace for sintering. The sintering conditions are the same, and subsequent steps 5 and 6 are no longer performed. After sintering, the powder is taken out and turned into a finished product.
[0088] After inspection and testing, the density of the sintered blank is 5.68 g / cm 3 , the sintering density is significantly lower than that of Example 2. This shows that Na2MoO4 is easy to melt in the Mo matrix during the sintering process to form vapor pressure, which hinders the sintering densification process of the Mo-based metal. At the same time, the powders of the upper, middle and lower regions of the Mo-Na tube target were marked as a, b and c, and the Na content was tested respectively. The test results were: a: 8.4%, b: 9.1%, c: 9.5%. The Na element has segregated, which affects the homogenization of the Na element in the Mo-Na tube target, thereby reducing the coating performance of the Mo-Na tube target.
[0089] Comparative Example 2:
[0090] The difference between Comparative Example 2 and Example 2 is that in step 6, the pressing process is carried out at room temperature.
[0091] After inspection and testing, the density of the sintered blank is 5.41 g / cm 3 , the sintered density is significantly lower than that of Example 2. This shows that under the premise that Na2MoO4 does not soften at room temperature, the compression ratio of the Mo-Na alloy tube target is very limited, and the large number of pores in the Mo-Na tube target ultimately leads to a low density of the tube target. Density is the main indicator of target sputtering coating performance, and a low-density tube target will inevitably lead to a decrease in the coating performance of the Mo-Na tube target.
[0092] Comparative Example 3:
[0093] The only difference between Comparative Example 3 and Example 2 is that in step six, there is no coating inside the pressing mold.
[0094] After inspection and testing, the density of the sintered blank is 5.82g / cm 3 , the sintered density is consistent with that of Example 2. However, it is very difficult to demold, and when demolding by hammering, the Mo-Na alloy sintered blank is partially deformed and falls off. This indicates that when there is no coating inside the pressing mold, the Mo-Na alloy blank cannot be demolded smoothly, which directly affects the yield of the Mo-Na alloy tube target.
[0095] In the above examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be purchased commercially.
[0096] It should be noted that although the present invention is described by the above embodiments, the present invention may also have other various embodiments. Without departing from the spirit and scope of the present invention, it is obvious that those skilled in the art may make various corresponding changes and deformations to the present invention, but these changes and deformations should all fall within the scope of protection of the appended claims of the present invention and their equivalents.
Claims
1. A method for preparing a molybdenum-sodium alloy target with high coating performance, characterized in that: The following steps are involved: Step 1: Select raw materials for preparing molybdenum-sodium alloy, mix them into mixed powder, and set aside, specifically: Selecting molybdenum powder and sodium molybdate powder as raw materials, dissolving the sodium molybdate powder in water to prepare a sodium molybdate aqueous solution, then mixing the molybdenum powder and the sodium molybdate aqueous solution to obtain a mixture, drying the mixture, grinding it, and sieving it to obtain a mixed powder; Step 2: placing the mixed powder of step 1 in a medium frequency sintering furnace for sintering to obtain Mo-Na alloy sintered powder for standby use; Step 3: Grind and sieve the Mo-Na alloy sintered powder obtained by sintering to obtain Mo-Na alloy powder for later use; Step 4: Put the Mo-Na alloy powder into a mold and press it to obtain a target blank for later use; Step 5: After processing the pressed target material blank, a finished Mo-Na alloy target material is obtained.
2. The method for preparing a molybdenum-sodium alloy target with high coating performance according to claim 1, characterized in that: The average particle size of the selected molybdenum powder is 2.2~4.2μm, the purity of the molybdenum powder is: 99.95%, and the purity of sodium molybdate is: 99%.
3. The method for preparing a molybdenum-sodium alloy target with high coating performance according to claim 1, characterized in that: Among the selected raw materials, based on mass percentage, the sodium molybdate content is 3.1%-31.3%, and the molybdenum powder content is 68.7%-96.9%.
4. The method for preparing a molybdenum-sodium alloy target with high coating performance according to claim 1, characterized in that: The molybdenum powder and the sodium molybdate aqueous solution are mixed using a solid-liquid mixer for 12-24 hours.
5. The method for preparing a molybdenum-sodium alloy target with high coating performance according to claim 1, characterized in that: The mixture is placed in a vacuum oven for drying. The drying conditions are: temperature 200±20℃, drying time 4-10 h; a 200-mesh screen is used for screening.
6. The method for preparing a molybdenum-sodium alloy target with high coating performance according to claim 1, characterized in that: In step 2, a medium frequency sintering furnace in a hydrogen atmosphere is selected, the sintering temperature is 900-1300°C, and the temperature is kept for 1-2 hours.
7. The method for preparing a molybdenum-sodium alloy target with high coating performance according to claim 1, characterized in that: In step 3, a 160-mesh screen is used for screening.
8. The method for preparing a molybdenum-sodium alloy target with high coating performance according to claim 1, characterized in that: In step 4, the mold is pressed by a hydraulic press, and the inner surface of the mold is covered with a MoS2 coating with a coating thickness of 0.2-0.4 mm.
9. The method for preparing a molybdenum-sodium alloy target with high coating performance according to claim 1, characterized in that: In step 4, the pressing temperature is 550°C-650°C, the pressing pressure is 50Mpa-130Mpa, and the holding time is 10-30min.
Citation Information
Patent Citations
Preparation method of molybdenum-sodium alloy composite powder
CN117620191A
Low-temperature rapid sintering preparation method of sodium molybdenum ceramic target material
CN118324524A